1999
DOI: 10.1164/ajrccm.160.5.9903015
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Failure in Patients with Severe Community-acquired Pneumonia

Abstract: In uncontrolled studies, noninvasive positive pressure ventilation (NPPV) was found useful in avoiding endotracheal intubation in patients with acute respiratory failure (ARF) caused by severe community-acquired pneumonia (CAP). We conducted a prospective, randomized study comparing standard treatment plus NPPV delivered through a face mask to standard treatment alone in patients with severe CAP and ARF. Patients fitting the American Thoracic Society criteria for severe CAP were included in presence of ARF (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
284
6
23

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 546 publications
(341 citation statements)
references
References 39 publications
17
284
6
23
Order By: Relevance
“…In one trial, patients with COPD were included, and results for patients who did and did not have this condition were reported separately. 38 In the subgroup of patients who did not have COPD (n = 33), the addition of noninvasive positivepressure ventilation did not reduce endotracheal intubation (6/16 v. 8/17 in control group) or hospital mortality (6/16 v. 4/17). In the other trial, which involved patients with acute hypoxemic respiratory failure but no underlying COPD, there was benefit (reduced endotracheal intubation and ICU mortality) for the subgroup of patients (n = 34) with severe communityacquired pneumonia.…”
Section: Statementsmentioning
confidence: 86%
See 1 more Smart Citation
“…In one trial, patients with COPD were included, and results for patients who did and did not have this condition were reported separately. 38 In the subgroup of patients who did not have COPD (n = 33), the addition of noninvasive positivepressure ventilation did not reduce endotracheal intubation (6/16 v. 8/17 in control group) or hospital mortality (6/16 v. 4/17). In the other trial, which involved patients with acute hypoxemic respiratory failure but no underlying COPD, there was benefit (reduced endotracheal intubation and ICU mortality) for the subgroup of patients (n = 34) with severe communityacquired pneumonia.…”
Section: Statementsmentioning
confidence: 86%
“…We also report recommendations on technical strategies to optimize the use of noninvasive ventilation (e.g., interfaces, mode). See Table 2 38 whereas almost all other trials involving patients with exacerbation of COPD excluded patients with pneumonia. In that trial, 38 use of noninvasive positive-pressure ventilation was associated with a reduction in endotracheal intubation (0/12 in intervention arm v. 5/12 in control arm, p = 0.005).…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…Embora comprovada primeiramente em doenças como exacerbações agudas de doença pulmonar obstrutiva crôni-ca [42][43][44][45] , edema pulmonar cardiogênico agudo 46-48 e insuficiência respiratória pós-operatória 49,50 , o uso da VNI na insuficiência respiratória aguda também foi descrita em pacientes imunodeprimidos 51,52 , com pneumonia 53 , com interrupção ou falha na extubação 54 Ventilação não-invasiva em crianças -Loh LE et al…”
Section: Aplicação Da Vni Em Casos Agudosunclassified
“…Estudos com adultos não mostraram um argumento convincente a favor da VNI nos quadros de pneumonia adquirida na comunidade 53 . Os estudos pediátricos existentes podem ser mais promissores.…”
Section: Pneumoniaunclassified
“…More recent studies have confirmed high failure rates in patients with pneumonia and severe ARF (27,(30)(31)(32). The only prospective randomised clinical trial (RCT) in the literature that compared conventional treatment with or without NIV demonstrated that patients who had received NIV together with conventional treatment had lower rate of tracheal intubation and a shorter stay in the intermediate care unit than those who received conventional treatment only, although the length of hospital stay and hospital mortality were similar between both groups (33). This study also showed in a subset analysis that the significant benefits of NIV occurred in patients with COPD and hypercapnic respiratory failure only; this subset of patients had also a lower mortality after two months.…”
Section: Severe Community-acquired Pneumoniamentioning
confidence: 99%